2019
DOI: 10.32607/20758251-2019-11-2-98-101
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage MS2 As a Tool for Targeted Delivery in Solid Tumor Chemotherapy

Abstract: Bacteriophage MS2 was employed for targeted delivery of an apoptosis-inducing agent, Tl+, into a tumor tissue. The targeted delivery was ensured by iRGD peptide, a ligand of integrins presumably located on the surface of endotheliocytes of the tumor tissue neovasculature and certain tumor cells. The synthesized peptide was conjugated to MS2 capsid proteins. Tl+ ions from TlNO3 penetrated the phage particles and tightly bound to phage RNA. Peptide-modified MS2 preparations filled with Tl+ caused cell death in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…For that reason, a multi-epitope-based peptide vaccine can be designed with immunogenic proteins of a pathogen. In the present scenario, a large number of peptide vaccines are in progress, majority of which are for human infectious diseases and tumor (55)(56)(57)(58). Very few studies are reported in the field of in silico vaccine for poultry and animals.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, a multi-epitope-based peptide vaccine can be designed with immunogenic proteins of a pathogen. In the present scenario, a large number of peptide vaccines are in progress, majority of which are for human infectious diseases and tumor (55)(56)(57)(58). Very few studies are reported in the field of in silico vaccine for poultry and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Phage-based therapies, as well as phage lytic-enzyme therapies, have been reported. The effects of phages on cancer cells in vitro as well as in vivo are promising [ 8 , 9 , 10 , 11 , 12 ]. Similarly, hybrid phages or modified phages have been developed by various groups worldwide to specifically detect, target, and attack different cancer cells including PCa [ 10 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cargo capacity: Phages are proven to carry wide variety of cargoes that ranges from small dyes to large DNA molecules. Phages have efficiently carried diverse payloads such as fluorescent dyes, photosensitizers, QDs, other small nanoparticles, protein drugs, chemotherapeutic drugs, siRNA, CRISPR-Cas, and large mammalian gene expression cassette [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Due to their natural evolution in carrying their own large genomes, phage vectors can be manipulated to encapsidate large genes/genes of interest by synthetic genetic engineering techniques; further, due to safety concerns related to mammalian viral vectors, the safe-to-human phage vectors are now being considered as suitable alternatives.…”
Section: Amenable Phage Featuresmentioning
confidence: 99%